Medical Devices and their Role in Supporting the Digestive System in Cases of Intestinal Failure - Hassan, Sajjad Allawi; Laith Hadi, Mohammed Al-Sadiq; Sulaiman, Hashim Abdulhakeem; thamer, Ali adnan (American Journal of Botany and Bioengineering, 2025)
An artificial organ could replace many functions of gut, but only can assist or replace a few functions. In the human body, the exocrine functions of the liver, pancreas, and intestine contribute to its assist digestion, and further the cellular functions of the liver and bone marrow have effects on this digestion and absorption condition in the body. An artificial organ can replace the insulin secretion function of pancreas, gall secretion function of liver, substitution in parenteral nutrition (PN) or the absorption function of intestine, but it only assist the digestion function of the intestine to some extent. Consequently, development of an artificial device that can substitute as many of these functions as possible could be anticipated to facilitate complete digestion of food taken by the mouth, and will advance the quality of life, as well the activity of other artificial organs. In the living human body, the efficiencies of exocrine functions of the intestine, liver, and pancreas are of course good. Additionally, the ingested food substance is significantly small. Consequently, it is quite difficult to completely substitute these functions by an artificial device. Alternatively, the device may replace only one or a few, and effort has been made to do so. In the ancient human body, of the entire volume of the stomach and the small intestines is given to assist or complete the digestion and absorption of food. In the case of human or other animal under serious intestines weakens by reason of the disease, the amount of intake is limited, since normal digestion and absorption are difficult [1]. In such case, as a treatment method, a transplantation of the artificial intestine into the body is considered whereby it may be possible to safe the life of patient. In the present, small intestine transplantation as a clinical case is performed. It is also considered for artificial intestine to be transplanted into the body. Hooking up of such a transplantation was discussed. On the other hand, there are means as may assist the digestion and the absorption even if not transplantation.